Gen Z sebagai Collaborative Achiever: Analisis Faktor Motivasi Belajar Mahasiswa Manajemen Universitas Islam Bandung - Aditia Wirayudha; M. Arif Rahmadha Darma Putra KM; Allya Roosallyn Assyofa; Indah Himawat Pertiwi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Figuring out what motivates Gen Z is interesting since it means that learning techniques and goals must be in line with what makes Gen Z special. This study seeks to delineate the framework of students' motivational variables in lecture activities, grounded in McClelland's theory of wants, which encompasses the need for accomplishment, power, and affiliation. The research was performed on students enrolled in the Management Study Program at Bandung Islamic University, employing a quantitative methodology and the Exploratory Factor Analysis (EFA) technique. Data were gathered via a questionnaire employing a Likert scale, administered to 89 respondents picked through a simple random sample method. The analysis reveals four primary factors that affect students' learning motivation: (1) Achievement-Oriented with Social Control, indicating a drive to enhance performance, obtain feedback, and derive satisfaction from accomplishments; (2) Powerful Achievement, reflecting a desire to lead, assume responsibility, and confront challenges; (3) Social-Collaborative, encompassing the need for acceptance, social interaction, and collaboration; and (4) Achievement with Competitive Drive, focused on reaching objectives and fostering competition. These four factors account for 61.812% of the overall variance in student learning motivation. The findings of this study present a student motivation profile characterized as a